A Qualitative Analysis of Pesantren Educational Management: School Culture and Leadership of a Professional Learning Community - Nyimas Mu'azzomi; Muhammad Sofwan; Fachrudiansyah Muslim (Ta'dib: Jurnal Pendidikan Islam, 2017)
The purpose of this paper is to explore supportive and shared leadership structures at one Indonesian Islamic boarding school (Pesantren) as a function of school culture policies and procedures in a professional learning community in the disctrict. A qualitative study was conducted at one Pesantren located in Jambi, an Indonesian province in west part of Sumatra island. We interviewed three administrators and five teachers to get in-depth information about the purpose of this paper. The interview transcriptions were translated, coded, divided into themes, and elaborated in the findings of the paper. The findings of study conclude that Pesantren leaders in the perspective of the participants must provide supportive and shared leadership structures for teachers in order to create positive cultures and effective a professional learning community for the development of the Pesantren. Leaders of the Pesantren must directly cooperate with teaching staff to provide policies and procedures for teachers in the leadership structure to directly impact school improvement through professional learning community collaborative attempts. This study was conducted based on the school culture and professional learning communities literature by exploring existent policies and practices in schools as unique cases. This study is significant to the community as specific cases informing educational leaders especially in Islamic education on mechanisms that may be leveraged to ensure successful implementation of policies and procedures on the leadership and school culture of a professional learning community literature.